OPTIMIZATION OF CONFIGURATION OF INDUSTRIAL ETHERNET NETWORKS DURING DESIGN OF THE AUTOMATED PRODUCTION MANAGEMENT SYSTEM - V. A. Kholopov; E. N. Kashirskaya; M. V. Gusev (Российский технологический журнал, 2018)
The paper considers optimization of industrial network configuration based on industrial network simulation. A description of step-by-step industrial network design including algorithmic and mathematical models is given. An algorithm for designing the APCS (Automated Process Control System) industrial network is developed, the metrics of the industrial network are compared with the factors affecting them, and the optimization objective function is developed. A solution of the problem of combinatorial optimization of the industrial Ethernet networks is proposed. Boltzmann scheme annealing method is used as an optimization method that regulates a random search for a global minimum of the objective function. The developed optimization method is a promising solution allowing to increase the efficiency of the APCS industrial network project design. The results of using the method are: reduction of the number of errors at the working project creation stage; design process structuring; clear requirements formalization; saving man hours of qualified employees in drawing up topologies, specifications and other project documents; reduction of the system cost.